Isoenzyme variation and genetic affinities among four species of the genus Festuca L. (Poaceae) - Angelov, Georgi B.; Ivanova, Teodora A. (Biodiversity: Research and Conservation, 2013)
Festuca L. is one of the most complicated genera in Poaceae. Polyacrylamide gel electrophoresis was used to study the isoenzyme variation of glutamate-oxaloacetate transaminase, malate dehydrogenase, glutamate dehydrogenase, isocitrate dehydrogenase and 6-phosphogluconate dehydrogenase in natural populations of F. valesiaca Schleich. ex Gaud., F. rupicola Heuff., F. dalmatica (Hack.) K. Richt. and F. stojanovii (Acht.) Kozuharov ex Foggi & Petrova. The aim of the present study was to assess isoenzyme variation and genetic affinities among the four species of the genus Festuca. Genetic identities (I) and distances (D) were calculated to evaluate qualitative genetic affinities and systematic relationships among the species. Considering the patterns of isoenzyme variation in the studied group, it is evident that F. dalmatica and F. stojanovii are closely related species. The species F. valesiaca and F. rupicola are isoenzymatically well characterized as distinct genetic entities. The obtained results generally support recent narrow species concept in the genus Festuca.